Economic Empowerment of the Scrap Carpenter Community Based on Asset-Based Community Development in Kedunglosari Village, Jombang - Muhammad Nasrul Waton; Fathoni Fathoni; Abdullah Asyiq (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Abstract:The problem of waste management and the marginal economic conditions of the scrap collector community are the main background of this community service. The program aims to improve the economic welfare of the scrap collector community in Kedunglosari Village, Tembelang District, Jombang Regency through an Asset-Based Community Development (ABCD) approach. The method used includes five ABCD stages (Discovery, Dreaming, Design, Define, Delivery) with asset identification activities, Focus Group Discussions (FGDs), scrap sorting and processing training, and the formation of the Joint Business Group (KUB)